Peningkatan Kemampuan Menulis Laporan dengan Model Pembelajaran Berbasis Portofolio - Ratna Juita (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2018)
This study aimed to (1) describe the learning outcome of writing a report before a portfolio-based learning model of the students of class VIII B at MTs Negeri 2 Bengkulu was conducted, (2) describe the result of the learning model in writing a report after portfolio-based learning in class VIII B MTs Negeri 2 Bengkulu was conducted, (3) describe the improvement in the ability to write a report based on the portfolio-based learning model of the students of class VIII B at MTs Negeri 2 Bengkulu. (1) The research was an action research, with descriptive analysis technique. The results of this study were the mean of the result of the pre-test in writing report material was 64 in sufficient category and the percentage of classical mastery was 75%. (2) The mean score of the students’ discussion result on writing report subject with the portfolio-based learning model in the first cycle was 74 in medium category. (3) The mean score of students’ discussion result on writing report subject with the portfolio-based learning model in cycle II was 80 in good category. (4) The mean result of the post-test on writing report material with the portfolio-based learning model was 80 in good category. (5) The percentage of classical mastery was 100% achived in cycle II. (6) The portfolio-based learning model was accurate enough to be implemented in improving student learning outcome. The conclusion of this study was that the portfolio-based learning model was accurate enough to be implemented in improving student learning outcome. Keyword: The ability to write a report, portfolio-based learning model